Pengaruh Kompetensi, Independensi, dan Etika Profesi Terhadap Kualitas Audit Di Inspektorat Provinsi Gorontalo - Hasan, Meryanti; ., Saprudin; Masiaga, Novaliastuti; Abdullah, Julie; Hasan, Wahyudin (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to analyze the impact of competence, independence, and professional ethics on audit quality at the Inspectorate of Gorontalo Province. A quantitative approach was employed using a census sampling method, involving 54 auditors. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The partial test results show that competence, independence, and professional ethics each have a significant effect on audit quality. Auditors with high competence can accurately identify and report audit findings. Good independence ensures objectivity without external influence, and strong professional ethics maintain the integrity of auditors. The simultaneous test results indicate that these three variables collectively have a significant effect on audit quality, with an R square value of 0.661, meaning that 66.1% of audit quality is influenced by competence, independence, and professional ethics. This underscores the importance of strengthening these three factors to improve audit quality at the Inspectorate of Gorontalo Province.